Kajian Pustaka Efek Farmakologi Daun Srikaya (Annona squamosa L.) - Alpha Cindy Elora; Siti Hazar; Sri Peni Fitrianingsih (UNISBA Press, 2022)
Abstract. Medicinal plants are plants that one or all parts of the plant contain active substances that are efficacious for health and can be used as a healer of disease. One of the plants that has long been used and used as a traditional medicine is srikaya (Annona squamosa L.). Annona squamosa L. is one of the medicinal plants which is claimed to be beneficial for human health. A review of the literature on this plant needs further research to find various pharmacologycal effects. Chemical exploration for candied leaf extract was reported and contained many complex active phytochemicals. These secondary metabolites are important to further explore pharmacologycal effects. The extracted leaves of Annona squamosa L. have been identified as having antibacterial, antioxidant, anticholesterol, antipyretic, and antianthelmintic properties. This literature review emphasizes the systematic investigation of Annona squamosa L. in its pharmacologycal effects, which can be a source of impotence for a variety of human disorders. The results showed that there were 5 pharmacological effects of the leaf extract, namely antibacterial, antioxidant, anticholesterol, antipyretic, and antianthelmintic. Abstrak. Tanaman obat yaitu tanaman yang salah satu atau seluruh bagian pada tumbuhan tersebut mengandung zat aktif yang berkhasiat bagi kesehatan dan dapat dimanfaatkan sebagai penyembuh penyakit. Salah satu tanaman yang telah lama dimanfaatkan dan digunakan sebagai obat tradisional yaitu srikaya (Annona squamosa L.). Annona squamosa L. merupakan salah satu tanaman obat yang diklaim bermanfaat bagi kesehatan manusia. Kajian pustaka tentang tanaman ini perlu penelitian lebih lanjut untuk menemukan berbagai efek farmakologis. Eksplorasi kandungan kimia ekstrak daun srikaya dilaporkan dan mengandung berbagai fitokimia aktif yang kompleks. Metabolit sekunder ini penting untuk mengeksplorasi efek farmakologi lebih lanjut. Daun Annona squamosa L. yang telah diekstraksi telah diidentifikasi memiliki khasiat sebagai antibakteri, antioksidan, antikolesterol, antipiretik, dan antianthelmintik. Tinjauan pustaka ini menekankan penyelidikan sistematis Annona squamosa L. dalam efek farmakologis, yang bisa menjadi sumber impoten untuk berbagai gangguan manusia. Hasil penelitian menunjukkan bahwa terdapat 5 efek farmakologi dari ekstrak daun ini yaitu antibakteri, antioksidan, antikolesterol, antipiretik, dan antianthelmintik.